2021
DOI: 10.3390/ijerph18084033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Loving-Kindness Meditation on Doctors’ Mindfulness, Empathy, and Communication Skills

Abstract: Background: In the context of increasing doctor–patient tensions in China, the objective of this study was to explore and examine the effects of loving-kindness meditation (LKM) on doctors’ mindfulness, empathy, and communication skills. Methods: A total of 106 doctors were recruited from a hospital in China, and randomly divided into an LKM training group (n = 53) and waiting control group (n = 53). The LKM training group received 8 weeks of LKM training intervention, whereas the control group received no int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 68 publications
1
56
0
Order By: Relevance
“…In addition, it is important to avoid some subjects, especially for beginners, during the practice of compassion meditation. For example, the object of blessing cannot be the opposite sex, cannot be too close to oneself or have the same interests, cannot be a dead person, and so on, in order to ensure the purity of the feelings cultivated [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it is important to avoid some subjects, especially for beginners, during the practice of compassion meditation. For example, the object of blessing cannot be the opposite sex, cannot be too close to oneself or have the same interests, cannot be a dead person, and so on, in order to ensure the purity of the feelings cultivated [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown the impact of mindfulness-based intervention guidance on occupational mental health of medical staff. Health care providers are using mindfulness practices to address mental and physical stress, emotional distress and burnout, while improving empathy, job satisfaction and well-being [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Loving-kindness meditation is a special meditation to cultivate compassion ( Chen et al, 2021 ), and this kind of compassion is a kind of unconditional and undifferentiated goodwill to all living beings, that is, this goodwill is not affected by kinship or interest relations ( Liu et al, 2022 ). The main function of LKM is that it can be practiced to regulate real-time emotions in life when the mood is low, and long-term practice of LKM is conducive to long-term emotion regulation.…”
Section: Introductionmentioning
confidence: 99%